The effect of neurotrophic factors on morphology, TRPV1 expression and capsaicin responses of cultured human DRG sensory neurons. - Anand, U; Otto, W; Casula, M; Day, N; Davis, J; Bountra, C; Birch, R; Anand, P (2006)
We have studied the effect of key neurotrophic factors (NTFs) on morphology, levels of the vanilloid receptor-1 (TRPV1) and responses to capsaicin in adult human sensory neurons in vitro. Avulsed dorsal root ganglia (DRG, n = 5) were cultured with or without a combination of nerve growth factor (NGF), glial cell (line)-derived growth factor (GDNF) and neurotrophin3 (NT3) for 5 days. In the absence of NTFs, the diameter of neurons ranged from 20 to 100 microm (mean 42 +/- 4 microm). Adding NTFs caused a significant increase in neuronal sizes, up to 120 microm (mean diameter 62 +/- 5 microm, P < 0.01, t-test), an overall 35% increase of TRPV1-positive neurons (P < 0.003), and notably of large TRPV1-positive neurons > 80 microm (P < 0.05). Responses to capsaicin were significantly enhanced with calcium ratiometry (P < 0.0001). Short duration (1h) exposure of dissociated sensory neurons to NTFs increased numbers of TRPV1-positive neurons, but not of TRPV3, Nav 1.8 and IK1 and the morphological size-distribution remained similar to intact post-mortem DRG neurons. NTFs thus increase size, elevate TRPV1 levels and enhance capsaicin responses in cultured human DRG neurons; these changes may relate to pathophysiology in disease states, and provide an in vitro model to study novel analgesics.